Water mites of the genus Unionicola Haldeman, 1842 (Acari, Hydrachnidia, Unionicolidae) in Russia - Tuzovskij, Petr V.; Semenchenko, Ksenia A. (Zootaxa, 2015)
This study presents a detailed taxonomic review of water mites of the genus Unionicola Haldeman, 1842 (Hygrobatoidea: Unionicolidae) found in the fauna of Russia during the long-term survey period of 1969–2013. The review includes (re)descriptions and illustrations of 21 Unionicola species found in this country: Unionicola intermedia (Koenike, 1882), U. crassipes (O.F. Müller, 1776), U. rossica sp.n., U. figuralis (Koch, 1836), U. gracilipalpis (Viets, 1908), U. markovensis Tuzovskij, 1990, U. minor (Soar, 1900), U. hankoi Szalay, 1927, U. aculeata (Koenike, 1890), U. aculeatella sp.n., U. bonzi (Claparède, 1869), U. inusitata Koenike, 1914, U. rezvoi Sokolow, 1931, U. samaraensis sp.n., U. setipella sp.n., U. setipes Sokolow, 1931, U. tricuspis (Koenike, 1895), U. japonensis Viets, 1933, U. primoryensis sp.n., U. ypsilophora (Bonz, 1783), U. arcuata (Wolcott, 1898). A key is presented for the Unionicola species of Russia based on males and females.